Strategi Public Relations dalam Membangun Citra pada Kantor Kementerian Agama Kabupaten Sidoarjo - Nisa' Fiamanillah; Arum Sukma Sari; Ali Mustofa; Muchammad Nizar (Jurnal Administrasi Pendidikan Islam, 2024)
This research aims to understand public relations strategies in building the image of the Sidoarjo Regency of Ministry of Religious Affairs. This research is qualitative research, data collection techniques using interviews and observation. Meanwhile, in this research, the data analysis used is systematic and logical data carried out from the beginning of the researcher until the end. The research results show that the Sidoarjo Regency of Ministry of Religious Affairs has implemented a Public Relations strategy optimally. One way is through active communication with mass and social media, both by providing the latest information regarding the Sidoarjo Regency of Ministry of Religious Affairs. The subjects observed were employees of the Sidoarjo Regency Ministry of Religion in the general department, especially in public relations, optimizing work units under the leadership of the Sidoarjo Regency of Ministry of Religious Affairs. Keywords: Public Relations Strategy, Community Relations, Institutional Image. Abstrak: Penelitian ini memiliki tujuan untuk memahami strategi public relations idalam membangun icitra pada iKantor iKementerian iAgama iKabupaten iSidoarjo. iPenelitian iini merupakan ipenelitian ikualitatif, iteknik ipengumpulan data dengan imenggunakan wawancara dan iobservasi. Sedangkan pada ipenelitian iini, analisis idata yang digunakan adalah idata yang sistematis dan logis yang dilakukan pada awal peneliti datang hingga akhir. Hasil penelitian menunjukkan bahwa Kantor Kementerian Agama Sidoarjo telah mengimplementasikan strategi Public Relations dengan optimal. Salah satunya adalah melalui komunikasi aktif dengan media massa dan sosial, baik dengan menyediakan informasi terbaru terkait Kantor iKementerian iAgama iKabupaten iSidoarjo. Subyek yang diamati adalah pegawai Kementerian Agama Kabupaten Sidoarjo dibagian umum terutama pada humas melakukan optimalisasi satuan kerja yang berada dibawah pimpinan Kantor Kementerian Agama Kabupaten Sidoarajo. Kata Kunci: Strategi Public Relations, Hubungan masyarakat, Citra.